Feeding of arctic cod, walleye pollock, and other pelagic fish and their food supply in the Chukchi Sea in August-September, 2019 - N. A. Kuznetsova; K. M. Gorbatenko (Известия ТИНРО, 2021)
Data on feeding of fish are presented collected in the western Chukchi Sea aboard RV «Professor Levanidov» and in the eastern Chukchi Sea aboard RV «Ocean Starr» in August-September, 2019. The feeding was different by areas of the sea and reflected regional features of food base. Copepods and euphausiids were the main components of the diet, though their ratio varied. In the western Chukchi Sea, arctic cod and walleye pollock (40–70 cm) were the main consumers of food resources and consumed on average 3.85 and 8.38 t/km2  per day, respectively. The diet of walleye pollock included fish (4.05 t/km2 . day) and zooplankton (3.01 t/km2 . day, mostly euphausiids — 2.60 t/km2 . day). Arctic cod consumed predominantly zooplankton (3.00 t/km2 . day, mostly copepods — 1.27 t/km2 . day, but also small- and medium-sized species). The total stock of net zooplankton (55.2 t/km2 ) exceeded in 7 times daily consumption of zooplankton. Coelenterates, arrowworms, other plankton species, benthic species, and small-sized nekton were consumed by fish poorly. Daily food ration of arctic cod and walleye pollock was estimated as 7.4–9.4 % and 3.4–4.7 % of their body weight, respectively, so the food supply of these species in the western Chukchi Sea was quite sufficient in 2019. In the eastern Chukchi Sea, the diet of juveniles of walleye pollock, sand lance and arctic cod included mainly copepods (50.5 %), euphausiids (12.0 %) and oikopleura (17.0 %). Ratio of zooplankton stock to daily consumption was twice higher in the southern part of the eastern Chukchi Sea than in its northern part. The consumption was also higher in the southern area where the index of stomach fullness reached 114.8 ‱ for pollock juveniles and 262.0 ‱ for sand lance juveniles, whereas it was 87 ‱ for juvenile arctic cod and 47 ‱ for juvenile sand lance in the northern area.